Strongyloidiasis in a Patient Diagnosed by Metagenomic Next-Generation Sequencing: A Case Report - Qu, Junyan; Zong, Zhiyong (Frontiers in Medicine, 2022)
Background: Strongylodiasis may be asymptomatic or cause mild gastrointestinal symptoms, and may be a fatal disseminated disease or Strongyloides hyperinfection syndrome. Non-specific clinical manifestations, such as pneumonia and gastroenteritis, pose a diagnostic dilemma. Case presentation: We report a case of a 67-year-old Chinese male who presented with abdominal pain, fever, headache, vomiting, constipation, and slight cough with sputum for nearly two months. He had been in good health and had no history of glucocorticoid use. He was diagnosed with enterococcal meningitis and intestinal obstruction at a local hospital and improved after treatment with vancomycin, but symptoms of headache and abdominal pain soon recurred. The metagenomic next-generation sequencing (mNGS) of the cerebrospinal fluid using Illumina X10 sequencer revealed 7 sequence reads matching Strongyloides stercoralis. Strongyloidiasis was suspected. Microscopic examination of gastric fluid revealed the presence of S. stercoralis larvae, which was confirmed by PCR to amplify both S. stercoralis ribosomal DNA gene and mitochondrial cytochrome c oxidase subunit 1 gene and sequencing amplicons. Strongyloidiasis was diagnosed. Albendazole (400 mg, twice daily) was used, and the patient recovered gradually. Conclusions: mNGS may be a useful tool for detecting uncommon infectious disease. The case would help clinicians to raise awareness of strongyloidiasis in non-endemic areas and reduce fatality.